THE PECULIARITIES OF REORGANIZATION OF HIGHER MEDICAL EDUCATION SYSTEM IN THE LIGHT OF THE BOLOGNA PROCESS - Стоцький, C. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The development of Ukrainian medical education, which is aimed at training the highly qualified physician who meets modern level of development of medical science and the demands of society is based on the introduction of qualitatively new methodology of educational process on the European model. The concept is founded on the European trends and national strategy. The development and improvement of higher medical education according to modern requirements should ensure Ukraine's integration into the international scientific and educational space and the Bologna Process. The quality of vocational education is essential to the development of modern education. The reform process of modern vocational education of Ukraine actualizes the problem of improving the quality of undergraduate and postgraduate training [1, 3].The basic principle ofbuilding the content of medical education in Ukraine is the focus on the end goal and competence approach, the implementation of which is carried out due to the credit-module system that provides conditions for active participation of students in the educational process on the basis of a fullfledged partner of interaction with the teacher, the increase of their individual work, extension of the opportunities for individualization of the learning process and so on.